Mobile Quran app security vulnerabilities - Talib, Shuhaili; Mahmud, Murni; Abd Rahman, Emilia Sarah; Songib, Anis Suraya; Ibrahim, Adamu Abubakar (School of Computing, Universiti Utara Malaysia, 2015)
The security threats and vulnerabilities of mobile Quran appli-cations can be viewed from both developers’ and a service perspective. Sim-ilar to other apps categories like entertainment apps, games apps, banking apps and many others, understanding the threats and vulnerabilities of mobile Quran apps and the ways to manage them is crucial. With regard to the rapid transformation of many services and transactions onto mobile platforms, the security awareness of these becomes very important. Developers are respon-sible for ensuring that they have the necessary tools they need to build secure mobile apps which will secure and protect end user privacy and ensure relia-ble service delivery. Mobile Quran apps that provide features for enabling reading the Quran and interacting with other add-ons prolific events, like an easy and fast surah index list, efficient search features and many more need to be protected. Any attempt that could compromise the originality of the con-tent of the Quran which is built for mobile apps needs to be identified. Unfor-tunately the security vulnerabilities within these features that convey the con-tents of the Quran are not clear, and there is a lack of noticeable security threats and vulnerabilities from previous studies. This paper examine the cat-egory of mobile Quran app and investigates its security threats and vulnera-bilities. The outcome indicates measures to ensure that end users get the mo-bile Quran apps they need without compromising their privacy.